On some solutions of the Schröder equation in Banach spaces - Walorski, Janusz (Annales Mathematicae Silesianae, 1994)
The aim of this paper is to prove results on solutions of the Schröder equation (1) defined on cones in Banach spaces and having some properties connected with monotonicity and boundedness.